A blockchain model connecting electricity market and carbon trading market - Yi Wang; Lijuan Feng; Lin Wang; Weiqiu Yu (Alexandria Engineering Journal)
Many countries adopt carbon trading mechanism as the main policy tool to control carbon emissions. Although carbon trading systems have been established, there are still some ongoing problems such as inconsistent carbon accounting standards, data distortion and inefficient overall process within these systems. We propose an innovative blockchain model that integrates the carbon trading system, initial carbon allowance allocation by regulatory authorities, electricity consumers, and power generation firms into a unified framework. By connecting these components, the model facilitates government regulation, emission reduction by electricity companies, electricity purchasing by consumers, and trading of surplus carbon allowances in the carbon market. The key innovations of our model include the establishment of a standardized carbon accounting system, enhanced data transparency to reduce the risk of data falsification, and a two-stage differential game framework that optimizes social welfare through effective control of total carbon emissions. Our simulations demonstrate that this blockchain system can effectively stabilize carbon emissions at a desirable level, thereby contributing to more efficient pollution control.